The Preference of Domestic Tourist Towards the Tourism Destination During Pandemic Period in Bali - Octanisa, Dheanita Sekarini; Bendesa, I Komang Gde; Suryawardani, I Gusti Ayu Oka; Wiranatha, Agung Suryawan (E-Journal of Tourism, 2022)
The COVID-19 Pandemic that occurred around the world had an impact on the decrease in people's income which has implications for changing behavior in choosing tourist destinations. This study aims to: 1) analyze the relative importance attribute from Indonesian tourists who came to Bali during the COVID - 19 Pandemic 2.) Get the most optimal combination of tourist destination products choice based on the preferences of Indonesian tourists during the COVID – 19 Pandemic. The research was conducted at Benoa Harbour, I Gusti Ngurah Rai Airport and Kuta Beach from January to April 2021 through the dissemination of questionnaires to 160 Indonesian tourists by accidental sampling. Data analysis by conjoin method and analyzed with SPSS 2.0 program. The results showed that the relative importance attribute sorted from the highest value to the lowest value is cleanliness, price, attractiveness, service, recommendations, security, and promotion. Tourists' preference is the willingness of hygiene facilities, the price of > Rp.50.000, flexible artificial tour booking, friends/family, low case rates and discounts on airline tickets. Keywords: importance; preferences; travel; Bali.